Intimacy and isolation - McGraw, John G. (Value Inquiry Book Series, 2010)
This interdisciplinary book concerns personality, especially intimacy, principally love, and its absence in states of aloneness, primarily loneliness. The author argues that normal and preeminently supranormal personalities are chiefly constituted by intimate connections. Correspondingly, he proposes that the serious shortage of such shared inwardness is the nucleus of every type of personality abnormality.